ANALISIS PREFERENSI PETANI TERHADAP KARAKTERISTIK TEKNOLOGI PADI LADANG (KASUS DI KABUPATEN LAMPUNG TENGAH DAN LAMPUNG SELATAN, PROPINSI LAMPUNG) - KURNIA SUCI INDRANINGSIH; WAHYUNING K. SEJATI; SRI WAHYUNI (SOCA: Jurnal Sosial Ekonomi Pertanian, 2005)
Rice is important role as Indonesian main food. It takes share 25-30% fromtotal household expenses. But, government programs still can’t fulfill farmers’ need,because the dissemination of the program is still using delivery system approach.Effort to fulfill the needs is by an acquisition system that pointed toward farmers tolook for technology from the information source. The main characteristic of thissystem are: (1) bottom up approach, (2) horizontal hierarchy, and (3) participated andinteractive technology transfer. This paper aims to explain: (1) technologyclassification used by farmers; (2) Farmers’ preference and reason to chooseappropriate technology, according to technique, economic, social-culture, andsustainable aspects; and (3) technology characteristic used by farmer to optimize theachieved production and productivity. The results of this study indicated that thelocal and adaptive technology used by farmers was conducted by cultured approach.Technology applied by farmers can be classified: (1) local technology (39-77%),adaptive technology (20-23%); and advanced technology (3-38%). The priority scaleof rice technology criteria preferred by farmers was economic (0.33), sustain (0.32),technique (0.23) and social-culture (0.12). Component technology prioritized wasfertilization, disease protection, and post harvest, with priority scale of eachcomponent 0.24; 0.19; and 0.13. This study was also recommended that to increaserice production, “embung” technology could be introduced to the farmers, besidesorganic farming must be encouraged. Applied technology is gained based onphilosophy, tradition, and other social aspect, which becomes farmer’s motivator.